Implementasi Teknologi Virtual Reality sebagai Media Pembelajaran Bahasa Indonesia di Pusdiklat Bahasa Badiklat Kemhan - Ahmad Fahri (JURNAL PENDIDIKAN DAN PELATIHAN PERTAHANAN, 2024)
Along with advances in technology, learning media is also developing rapidly. There are many technologies designed to aid learning. One of the technologies introduced in the teaching and learning process is virtual reality (VR). This research discusses the implementation or use of VR technology in teaching Indonesian as a Foreign Language (BIPA) using the Virtual Reality Language application in the Virtual Reality Laboratory of the Badiklat Kemhan Language Education and Training Center. Qualitative research takes the form of a case study with a narrative research design as the main design and observation as the data collection method. In the results and discussion, the author provides general information about virtual reality technology and its appearance. Furthermore, the author describes how VR technology helps and provides benefits for students and what problems may occur during the learning process through VR technology